Advancements in Medical Image Segmentation Using the Minkowski Algorithm - Ruchi Bhardwaj; Shanu Gour (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Image segmentation refers to dividing an image into distinct segments or regions. It is important to distinguish between image parts and their alteration. The image fragmentation process focuses on segmenting the image based on its visual features such as brightness, contrast, and texture. In this segmentation approach, specific areas of the image are emphasized according to the given criteria. This paper will explore the effectiveness of different techniques applied to various types of images. The field of medical imaging is continuously evolving, with ongoing advancements in techniques and software aimed at improving the quality of healthcare services. The processes involved in tasks such as interpolation, image recognition, and resizing require further development to meet the increasing demands of the industry, as well as emerging technologies in mobile and cloud computing. The integration of medical devices and software with shareable platforms is also creating opportunities for further exploration. This paper provides valuable insights into the components of medical image segmentation systems and aims to explore the long-term potential of these segmentation methods.